Turbinoplasty by laser (Bangladesh Journal of Otorhinolaryngology, 2010)
This is a study of 61 cases of turbinoplasty done in 3 hospitals of Bangladesh from August2007 to July 2009 (2 years). This study compares turbinoplasty by laser with that of non-lasertechniques. 60.65% of patients were operated by laser and 39.34% of patients were operatedby non-laser techniques. Majority of the patients were from 21- 40 years of age, (62.16% inlaser group and 54.16% in non-laser group). Male & Female patients ratio was 3:1 in bothgroups. 100% of the patients were presented with nasal obstruction. 98.36% with nasaldischarge, 95.08% with headache and 75.40% with frequent sneezing (p